Detection of P30 Gene to Diagnosis of Toxoplasmosis by Using Polymerase Chain Reaction - Lisawati Susanto; Taniawati Supali; Srisasi Gandahusada (Makara Journal of Health Research, 2016)
Toxoplasma gondii is an intracellular protozoan which causes toxoplasmosis. In healthy persons (immunocompetent) the infection is usually asymptomatic; however in immunocompromised patients, especially AIDS patients, the infection can be fatal. Primary infection in pregnant women can be transmitted to the fetus via the placenta. Therefore laboratory examination is absolutely neccesary to assess the presence of T.gondii infection hence prompt treatment can be given to prevent further damage. The aim of this study is to know whether by using P30 gene as target the Polymerase chain reaction (PCR) can detect T.gondii DNA in Indonesia. The PCR was performed on the DNA which had been isolated against P30 gene as target by using the method described by Weiss et al and Chang & Ho. The P30 gene primers consisted of oligo 1: 5'CACACGGTTGTATGTCGGTTTCGCT3 and oligo 2: 5'TCAAGGAGCTCAATGTTAC GCT3. The DNA samples used in the PCR with P30 gene as target were derived from the following materials: (a) pure T.gondii DNA of various concentrations, (b) a mixture of pure T.gondii DNA and normal human blood DNA, (c) tachyzoite DNA derived from the mixture of 99 ml normal human blood and 1 ml tachyzoite suspension with the following amount of tachyzoites :1000,100, 50, 40, 30, 20 and 10 tachyzoites. It was shown that no specific bands were observed in the PCR with P30 gene as target (performed according to the method described by Weiss et al). The PCR according to the method described by Chang & Ho did not show any band when 30, 35, 40 and 45 cycles of PCR were used however, by using 50 cycles a specific band was observed. The results obtained showed that the minimal DNA concentrations which still could be detected using P30 gene as target were as follows : 0.001 ng DNA in 50 ml PCR solution from samples of pure DNA, 0.025 ng DNA in 50 ml PCR solution from samples of pure DNA mixed with normal human blood and the amount of DNA originated from at least 20 tachyzoites. It was concluded that the assay using P30 gene as target could be used for detecting T.gondii DNA in Indonesia.